Strategi Pendidikan Inklusif Berbasis Nilai-nilai Hadis Nabi: Studi Kasus pada Anak Lambat Belajar - Putri, Febrina Dyah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine the synchronization between the values of the Prophet Muhammad’s ﷺ hadiths and the principles of inclusive education in the context of primary education, particularly for slow learners. This research employs a qualitative approach with a library research method, analyzing hadiths relevant to the principles of inclusivity and equitable treatment of learners. The findings reveal that the Prophet consistently demonstrated individualized and compassionate approaches toward his companions with different learning traits. These hadiths contain educational values such as justice, patience, compassion, and appreciation of each individual's unique potential. In the practice of primary education, these values can be applied through strategies such as multisensory media, personalized approaches, and the reinforcement of emotional and motivational support for students facing learning difficulties. Case studies from several madrasahs show that teachers who apply these strategies have, in effect, embodied the Prophet’s teachings in their pedagogical practices. Hence, this study concludes that the prophetic values embedded in hadiths are highly relevant in promoting inclusive education. The research recommends the integration of hadith values into teacher training curricula to foster learning environments that are fair, compassionate, and tailored to each student’s individual potential.